ANALISIS PELAKSANAAN FUNGSI SOSIAL TOKOH MASYARAKAT DI DESA RASAU JAYA TIGA KABUPATEN KUBU RAYA - Layardian, Meidrik; Rustiyarso, Rustiyarso; Ramadhan, Iwan (Universitas Tanjungpura, 2024)
The problem of this research is how community leaders provide guidelines for the community to behave and provide guidance to the community to establish a special control system for children in Rasau Jaya Tiga Village. . This study aims to find out how community leaders provide guidelines for behavior and provide guidance to the community to establish a child control system. The method used is a qualitative approach with a descriptive type, the informants are 5 people, namely 3 community leaders and 2 residents in Rasau Jaya Village. The data collection tool uses an observation guide, interview guide, and documentation, the results of the study show that the form of the social function of community leaders has been implemented, as evidenced by the people in Rasau Jaya Village have become a society that is tolerant of inter-religious people, obedient to worship and adhere to existing values. In the community, community leaders have also succeeded in educating children's character in providing meaningful values in community life and at school, and always providing encouragement and attention to children such as controlling children while they are studying, and motivating children.